The impact of selected aspects of life on the incidence of back pain in relation to age of patients - Jerzy Błyszczuk; Renata Błyszczuk (University of Applied Sciences in Tarnow, Poland, 2017)
Intodruction: The most common reasons for back pain in modern society include inadequate physical activity, obesity and lack of basic knowledge on the correct positions of the spine. There are also other reasons such as pathological changes including damage and degeneration of annular fibers in the spinal disk, posttraumatic back pain and incorrect posture. Materials and methods: On the basis of a survey study on the population of 240 individuals (120 males and 120 females) we aimed to answer the following questions: how body index, physical activity, type of profession and education level correlate with the frequency of back pain in relation to age. Furthermore, responders reported the most commonly injured spine regions and types of treatments. Results and conclusions: Obese individuals more often suffer from back pain. Moderate physical activity is beneficial on spine prophylaxis. Aging correlates with higher risk of back pain. Back pain is the most commonly reported in the lumbar region. Common painkiller medications and restricted physical activity represent main treatments of back pain. Visiting a doctor, physiotherapy and therapeutic massage are less common. These conclusions hold true for both males and females.